Evaluation of wood forest resources - Сторожук, Тетяна Миколаївна; Дружинська, Наталія Сергіївна (Technology audit and production reserves, 2016)
In the current economic conditions economic evaluation of forest resources takes on new importance, which requires determining the value of assets that owned or constant use of forestry enterprises during the reporting period. Formation of accounting information on the cost of forest resources will provide an opportunity to analyze the benefits of the use of forest resources and their participation in the formation of national wealth. Research of scientific papers suggests that most scientists prove the necessity and possibility of continuous evaluation of all types of forest resources. As the forest is a difficult subject for evaluation, therefore, to represent them in the accounting system and financial reporting, we offer the following facilities to carry out accounting of forests, namely land for forestry purposes; wood forest resources (for production stages); forest products, which comes as a result of felling of trees or collecting non-wood forest resources. Forest resource evaluation can be made by enterprise independently based on international and national accounting standards, and can be conducted by independent certified expert appraisers.